Bilateral Optic Neuritis Secondary to Nivolumab Therapy: A Case Report - Ömer Kartal; Erman Ataş (Medicina, 2018)
Pediatric glioblastoma multiforme is an uncommon and highly mortal brain cancer. New therapeutic treatments are being intensively investigated by researchers in order to extend the survival of patients. The immune checkpoint inhibitor nivolumab in the treatment of pediatric glioblastoma multiforme is currently under review; it is a human immunoglobulin G4 monoclonal antibody that works against the programmed cell death protein 1 receptor, designed to enhance an immunologic reaction against cancer cells. Herein, we describe the first report of a bilateral optic neuritis induced by nivolumab in a grade 4 glioblastoma multiforme patient.